A comparative study on anisotropy of additively manufactured CoCrNi medium-entropy alloys by hot isostatic pressing and ultrasonic impact treatment - Xiaolin Bi; Ruifeng Li; Bin Liu; Jiangbo Cheng; Dikai Guan (Materials & Design, 2024)
The anisotropy properties of samples in different direction is found in additively manufactured (AM) CoCrNi medium-entropy alloys (MEAs). In this study, the laser direct energy deposition AM CoCrNi MEAs have been subjected to two alternative processing methods: hot isostatic pressing (HIP) and ultrasonic impact treatment (UIT). The effect of HIP and UIT on the microstructure, grain orientation, grain boundary distribution, phase distribution and mechanical properties of AM CoCrNi MEAs were systematically studied. The results show that HIP decreased the partial mechanical anisotropy of AM CoCrNi MEAs, and YS was significantly reduced. The main reason is that the HIP induces the formation of large number of Cr2O3 particles, and transformation of low-angle grain boundaries (LAGBs) into high-angle grain boundaries (HAGBs). Surprisingly, both the yield strength (YS) and ultimate tensile strength (UTS) of the AM CoCrNi MEAs were increased when the UIT was added after every laser deposition of one layer (UIT-1). This is due to the combined effect of quasi-static loading and ultrasonic oscillations of UIT, which results in the dislocation multiplication and the formation of a large number of substructures. In addition, the above strengthening phenomena also lead to decrease partial mechanical anisotropy of AM CoCrNi MEAs.